TEENAGE MOTHERHOOD: CAUSES, IMPLICATIONS AND POSSIBLE INTERVENTIONS OF ADULT EDUCATORS AND SOCIAL WORKERS - Adeyemo, comfort wuraola; Aborisade, omolola grace (Journal of Continuing and Development Education, 2023)
This study investigated teenage motherhood, the causes, implications and the possible intervention by adult educators and social workers. It particularly examined the factors responsible for teenage motherhood, including illiteracy, poverty, child abuse, peer pressure, lack of parental care and government factors, particularly in rural communities of Ekiti State. The study also examined the implications for teenage motherhood on the teenagers, the child and the society at large. The study examined the interventions of adult educators and social workers in Ekiti State. Findings from the study revealed that adult educators will assist victims of teenage pregnancies educationally and socially and make them fit back to the society. It also revealed that social workers will create awareness for teenagers against unplanned pregnancy and provide helping tips for those who have fallen victims. The study recommended that government and parents should provide enabling environments for teenagers, particularly the girl child in schools. Also, social workers should provide